Effects of chronic intensive training on androgenic and cortisol profiles in premenarchal female gymnasts - Jaffre, C.; Lac, G.; Benhamou, C. L.; Courteix, D. (European Journal of Applied Physiology, 2002)
The effect of intensive exercise training on urinary androgen and cortisol excretions in prepubertal girls of various ages was tested in competitive premenarchal gymnasts (n=56) and in age-matched controls (n=53). Both sexual maturation and bone age were assessed. Urinary excretions of androstenedione, dehydroepiandrosterone sulphate (DHEA-S), testosterone and cortisol were determined by radioimmunoassay procedures. The gymnasts were taller [mean (SD) 138.3 (9.0) cm vs 144.7 (8.3) cm; P<0.001] and lighter [32.0 (6.9) kg vs 36.7 (8.2) kg; P<0.001], and had a lower percentage of fat mass [16.8 (2.2)% vs 22.5 (6.6)%; P<0.0001] than the controls. There was no difference between groups in urinary testosterone, cortisol and DHEA-S levels, while androstenedione levels were significantly lower in gymnasts than in controls [mean (SEM) 187.10 (18.00) nmol/24 h vs 256.50 (15.00) nmol/24 h; P<0.01). There was no difference in the regression slopes between the two groups for all hormonal values. In conclusion, these results suggest that during the prepubertal period, intensive training alters only urinary androstenedione concentrations in girls.